ISLAM DAN TANTANGAN MODERNISASI: IMPLIKASI ZUHUD DINAMIS DALAM PENANGGULANGAN KORUPSI - Mahmud Ishak (TAHKIM, 2020)
Zuhud is one of the teachings, or maqam in Sufism. Zuhud is often misunderstood as a cause of the decline of the Muslims. Because ascetic understood as the denial of the search for the material, and hatred toward world affairs. Even ascetic understood as a poor lifestyle. But the dynamic ascetic who taught in Islam, on the one hand still excites people who ascetic (zahid) worked diligently searching for the treasure, but on the other hand will not be greedy, even his property will be used for the common good. So, people who ascetic dynamic, will be spared from greedy mentality. Thus, ascetic dynamic in the context of modern life, can be used to tackle corruption in Indonesia. Because one of the causes of the rampant corruption, is a greedy mentality